Predictors and clinical complications associated with antiphospholipid antibodies in sickle cell disease - Rivera, Claudia Rodriguez; Srisuwananukorn, Andrew; Bajwa, Rizma Jalees; Gordeuk, Victor R.; Rauch, Joyce; Levine, Jerrold S.; Saraf, Santosh L. (EJHaem, 2023)
Although a higher prevalence of antiphospholipid autoantibodies (aPL) has been observed in some cohorts of sickle cell disease (SCD) patients, the clinical risk factors for the development of aPL and its associated complications remain unclear. In a retrospective study of 63 SCD patients, a lower hemoglobin concentration and higher white blood cell count were independently associated with an elevated aPL. SCD patients with elevated aPL had increased pregnancy complications (≥3 miscarriages, preterm delivery, pre‐eclampsia) and venous thrombotic events. Our findings suggest that SCD may predispose to the generation of aPL and that aPL itself may contribute to the vasculopathy of SCD. Prospective testing for aPL is warranted in patients with SCD.